Evaluation of a Destination for Film Tourism: Harput Case - Celik, Ozlem Cakar (Istanbul Univ Press, Istanbul Univ Rectorate, 2019)
Harput is a historical destination which is geomorphological location on a plateau to the north of Elazig Plain and Uluova in the Upper Euphrates Section of the Eastern Anatolia Region. Harput is the source of Elazig's local identity, cultural values, historical roots, and architectural codes. The current city of Elazig, born from Harput, was formed by moving the inhabitants of Harput to the Elazig Plain. However, Harput began to lose importance in terms of all aspects due to the abandonment or relocation and the new generation is unaware of Harput's culture. This might be considered as a prodigious loss in terms of our culture and values and injustice for future generations. Harput's culture, folklore, lifestyle, traditions, historical figures, and architectural features can only be understood and explained in Harput. Today, TV series and movies are important media tools and destinations are now used in TV series and films as a product. The aim of this study is to reveal the characteristics of Harput which may be subject to the film industry. To this end, the geographical characteristics of Harput, the mansions located in Harput, its local music style, and its historical figures were examined. This study, which consisted of a literature review and field observations, revealed Harput's physical and human geography characteristics in terms of film tourism.
1st Istanbul International Geography Congress -- JUN 20-22, 2019 -- Istanbul, TURKEY
Keywords: Harput; tourism; film tourism